Respuesta :

Answer:

64x^3-241x^2+296x-125

Step-by-step explanation:

Answer:

60x^3-253x^2+308x-122

Step-by-step explanation:

(4x-5)^3-(x^2+4x+1)(4x-3)

=64x^3-240x^2+300x-125-(x^2+4x+1)(4x-3)

=(4x)^3-3(4x)^2*5+3*4x*5^2-5^3

=64x^3-240x^2+300x-125

=-(4x^3+13x^2-8x-3)

=-(4x^3)-(13x^2)-(-8x)-(-3)

=-4x^3-13x^2+8x+3

=64x^3-240x^2+300x-125-4x^3-13x^2+8x+3

=64x^3-4x^3-240x^2-13x^2+300x+8x-125+3

=64x^3-4x^3-253x^2+300x+8x-125+3

=60x^3-253x^2+300x+8x-125+3

=60x^3-253x^2+308x-125+3

=60x^3-253x^2+308x-122

So the Answer is 60x^3-253x^2+308x-122.

God Bless, Hope it helps!!!!!!!

ACCESS MORE